Sustainable Polymers: A Review of Green Synthesis and Applications - Jeslin.D; Dr. Masilamani. K (The Bioscan, 2025)
Sustainable polymers are revolutionizing materials science by providing eco-friendly alternatives to traditional petroleum-based plastics. These polymers aim to reduce environmental challenges like plastic pollution, carbon emissions, and resource depletion. This review explores the advances in green synthesis methods, such as bio-based monomers, biocatalysis, green solvents, and metal-free catalysis, that reduce dependence on fossil fuels and promote biodegradability. Some of the most prominent materials discussed are PLA and PHA, which come from renewable feedstocks such as agricultural waste and non-food biomass. Although much promise is being held by these materials, scaling up, cost-effectiveness, and mechanical performance are significant challenges to their use. In the pharmaceuticals industry, polymers have revolutionized drug delivery systems, for example, by controlled drug release, improving their biocompatibility, and reducing side effects. Controlled biodegradation has been achieved through synthetic polymers such as PLGA and PEG, and natural polymers, like chitosan and alginate, give biodegradability with biological system compatibility. Examples of advanced drug delivery technologies include stimuli-responsive and mucoadhesive polymers, which show their great flexibility in targeted therapy. The findings emphasize the need for interdisciplinary collaboration to overcome economic and performance challenges in green polymer synthesis. Future directions include optimizing enzyme-based processes, diversifying feedstocks, and integrating sustainable lifecycle assessments. These advancements are pivotal in ensuring sustainable polymers' adoption in a circular economy while addressing pharmaceutical and industrial needs.